A Distinct Strain of Cowpea mild mottle virus Infecting Soybean in India. Issue 10 (18th May 2013) - Yadav, Manoj K.; Biswas, Kajal K.; Lal, Sanjay K.; Baranwal, Virendra K.; Jain, Rakesh K.
Abstract: Soybean crops showing systemic mottling, mosaic and leaf deformation were observed at high disease incidences (25.1–71.0%) in the kharif season of 2011 and 2012 in the experimental farm of the Indian Agricultural Research Institute (IARI), New Delhi. Symptomatic soybean leaves contained flexuous particles (650 × 12 nm), suggesting an infection by a Carlavirus . The causal virus was characterized as a strain of Cowpea mild mottle virus (CPMMV) on the basis of mechanical inoculation, whitefly transmission, seed transmission and sequencing of the viral genome. This is the first report of natural infection by a distinct strain of CPMMV in soybean in India.